Staff perceptions on implementing interprofessional education for undergraduate students in health, social work and education (Journal of Applied Learning and Teaching, 2024)
Pedagogic approaches which promote collaboration and communication across undergraduate student groups are important for nursing, medical, social care, and education programmes. However, academics’ perceptions of developing these events and examples of how to plan and implement learning opportunities of this nature remain infrequent within the existing literature. To address this gap, the current paper provides an analysis of academics’ reflections on designing, developing and delivering an innovative simulation-based interprofessional education (IPE) event organised across two universities. Academics involved in either the design and/or facilitation of the interprofessional event were invited to complete a reflective account of their experience. Eight academic members of staff completed a reflective account from which three themes emerged. Themes included communication, valuing others and organisation. These accounts suggest that simulation-based IPE can be a useful teaching and learning strategy. However, resourcing and organisational factors should be carefully considered when planning IPE events.